Dietary flexibility of western red colobus in two protected areas with contrasting anthropogenic pressure - Aleixo-Pais, Isa; Borges, Filipa; Sesay, Nazie; Songe, Mustapha; Cassama, Mamadu; Camara, Iaia T.; Ramos, Catarina; Barca, Benjamin; Turay, Brima S.; Swaray, Mohamed; de Barros, Aissa Regalla; Quecuta, Queba; et al. (Frontiers in Ecology and Evolution, 2023)
Food distribution and abundance can affect intra- and inter-dietary variation in non-human primates, influencing feeding ecology and altering behaviour. Natural and/or human-induced actions can influence the dynamics between primates and the environment, with associated impacts on socio-ecology and demography. This relationship in anthropogenic landscapes, however, is poorly understood. Here, we characterise the diet of the western red colobus (Piliocolobus badius) in both the better preserved Gola Rainforest National Park (GRNP, Sierra Leone), and in the fragmented forests of Cantanhez National Park (CNP, Guinea-Bissau), and evaluate biological, ecological and temporal differences. We use DNA metabarcoding to obtain high resolution dietary diversity data, and multivariate generalised linear models to investigate variation in the diet of this threatened primate. Dietary plant species richness was high in both protected areas, and the type of plants consumed varied significantly across seasons, space, and time. Although we identify dependence on a few key plants, red colobus in CNP consumed a higher average number of plant taxa than in GRNP, and 11% of the diet consisted of cultivated foods (e.g. mango). This is the first time a molecular approach has been used to investigate red colobus diet, and reveal dietary flexibility in degraded forests. Predicting the consequences of dietary change on long-term population persistence, however, remains a significant knowledge gap. Nevertheless, our results provide critical information to inform targeted regional conservation planning and implementation.